2020
DOI: 10.1186/s13047-020-0378-2
|View full text |Cite
|
Sign up to set email alerts
|

Walking and weakness in children: a narrative review of gait and functional ambulation in paediatric neuromuscular disease

Abstract: Background: Weakness is the primary impairment in paediatric neuromuscular diseases, impacting gait and gaitrelated functional activities in ambulant children affected by these rare and often degenerative diseases. Gait speed is an indicator of health and disability, yet gait is a complex, multi-faceted activity. Using the International Classification of Function, Health and Disability (ICF) model, assessment of gait and functional ambulation should consider the impairments, activity limitations and participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 95 publications
1
14
0
5
Order By: Relevance
“…During gait, children who ITW operated at more plantarflexed angles, but at longer fascicle lengths than TD children. This coincided with observed differences in the peak of the moment-angle and moment-length relationships, measured from MVCs, which showed that children who ITW had the greatest strength at more plantarflexed angles and an Equinus gait has previously been linked with ankle, knee and hip extensor weakness in other clinical populations (Hampton et al, 2003;Kennedy et al, 2020;Morozova et al, 2017;Wiley & Damiano, 1998).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…During gait, children who ITW operated at more plantarflexed angles, but at longer fascicle lengths than TD children. This coincided with observed differences in the peak of the moment-angle and moment-length relationships, measured from MVCs, which showed that children who ITW had the greatest strength at more plantarflexed angles and an Equinus gait has previously been linked with ankle, knee and hip extensor weakness in other clinical populations (Hampton et al, 2003;Kennedy et al, 2020;Morozova et al, 2017;Wiley & Damiano, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…to contribute to equinus gait (Hampton et al, 2003;Kennedy et al, 2020;Morozova et al, 2017;Wiley & Damiano, 1998). For children who ITW, there has been an indication that there may be some small effects of ankle joint weakness (De Oliveira et al, 2021); however, to our knowledge, muscle strength around the hip or knee joint has never been objectively studied in children who ITW.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showcases translational and longitudinal use of quantitative motor metrics for a genetic NDD. Clinically, quantitative gait research has gained traction across many NDDs and the idea to tailor attention on gait in preclinical studies is now also gaining momentum (IDDRC working group, AGENDA working group, personal communications) for Rett syndrome, neurofibromatosis, Down syndrome, and other NDDs (Hampton et al, 2004;Jequier Gygax et al, 2020;Kennedy et al, 2020;Layne et al 2018;Rahn et al, 2020;Summers et al, 2015;Wilson et al, 2020). Data from our work showed analogous measures of gait phenotypes in rodents that are being quantified currently in AS clinics (Jessica Duis MD, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…There are many articles describing gait being connected with different disabilities, such as cerebral palsy, amputation, or Charcot–Marie–Tooth disease, as well as a neuromotor delay [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Since typically developed children move in a different way, the normative data for this group of age are also desirable [ 5 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%